Using feature-based product modelling to integrate design and rapid prototyping - Campbell, Robert Ian (1998)
Rapid prototyping (RP) provides a means of producing physical models directly from computer aided design (CAD) data. The aim of this research was to determine the most effective method of integrating RP into the design process.